Repercussions of the COVID-19 pandemic on athletes: a cross-sectional study - Lopes, Lucas; Miranda, Vitor; Goes, Rodrigo; Souza, Gabriel; Souza, Giuliana; Rocha, Jessica; Cossich, Victor; Perini, Jamila (Biology of Sport, 2021)
The COVID-19 pandemic has presented significant challenges and implications for the sports community. Thus, this study aimed to describe the prevalence of COVID-19 in Brazilian athletes and identify the epidemiological, clinical, athletic, life and health factors associated with the disease in these individuals. A cross-sectional study was performed involving 414 athletes from 22 different sports using an online questionnaire from August to November 2020. The association between the athletes’ characteristics and COVID-19 was evaluated using a logistic regression model. The prevalence of COVID-19 was 8.5%, although only 40% of athletes reported having been tested. Being under 27 years of age (3-fold), having children (~5-fold), havinga teammate test positive for COVID-19 (2.5-fold), and smoking (14-fold) were associated with a possible higher risk of disease. Almost 20% of athletes self-reported musculoskeletal injuries during the period of the pandemic that was studied. Athletes with a university education (P = 0.02), a profession other than sports (P < 0.001), those from a low-income family (P = 0.01), and public health system users (P = 0.04) were significantly less frequently tested for COVID-19, whereas international competitors, athletes who received a wage, and athleteswho had a teammate who tested positive for COVID-19 were 2-, 3-, and 15-fold more likely to be tested for COVID-19, respectively. Approximately 26% of the athletes who tested negative or were untested reported more than three characteristic COVID-19 symptoms, and 11% of athletes who tested positive for COVID-19 were asymptomatic. The identification of modifiable (have children, smoking, and teammates positively tested) and non-modifiable (age under 27 years) factors related to COVID-19 in athletes can contribute to implementing surveillance programmes to decrease the incidence of COVID-19 in athletes and its negative impacts in sports.